Optical Filters Utilizing Ion Implanted Bragg Gratings in SOI Waveguides. (10th April 2008) - Bulk, M. P.; Knights, A. P.; Jessop, P. E.; Waugh, P.; Loiacono, R.; Mashanovich, G. Z.; Reed, G. T.; Gwilliam, R. M.
Abstract : The refractive index modulation associated with the implantation of oxygen or silicon into waveguides formed in silicon-on-insulator (SOI) has been investigated to determine the feasibility of producing planar, implantation induced Bragg grating optical filters. A two-dimensional coupled mode theory-based simulation suggests that relatively short grating lengths, on the order of a thousand microns, can exhibit sufficient wavelength suppression, of> 10 dB, using the implantation technique. Fabricated planar implanted slab-guided SOI waveguides demonstrated an extinction of− 10 dB for TE modes and− 6 dB for TM modes for the case of oxygen implantation. Extinctions of− 5 dB and− 2 dB have been demonstrated with silicon implantation.